(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2024)
Understanding the productive structure of a territory and its evolution is essential when evaluating and designing development policies and effective private strategies. The objective of this work is to describe and analyze the evolution of the gross added value of La Pampa, throughout the period 2004-2021. Likewise, it seeks to obtain trends and a comparative analysis between provinces and nation. The main results can be observed the concentration of production in a few provinces, with a low participation of La Pampa. At the per capita level, there are other provinces with a higher order of importance. Regarding the sectors, the importance of the trade and agricultural items in La Pampa is raised. While at the national level the influence of the industry differs. A moderate level of concentration is presented by the sectors that make up the gross added value.